The implementation of international treaties of Human Rights in Argentina. Part II: Interventionist model of the 2003-2011 - Parisí, Elio Rodolfo; Manzi, Adrian (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The Inter-American Court of Justice has ruled failures in many cases concerning violations of human rights in Latin America, efectivizando the real value of the ratification of international human rights treaties and forcing each State to take direct and concrete measures to compensate the rights violated. In this second part will analyze the formal system of right times function as intimidation of power in the case of Argentina, as part of the game between the mechanics of the discipline and knowledge of the law. We believe that the Argentine judges not interpreted solely in accordance with the rules established constitutionally, but also the axiological system which carries is applied in the light of the strength or weakness of the sectors involved, being the time the balance decreed that these characteristics with which to weigh the influences. Through the question: what is the system of law but the domain will?, we continue with the relations of force foucauldian analysis, considering our society as normalization, that soberaniza and discipline, regulates the force relationships through civil society and the judicial system.